Knowledge and Attitude of Cervical Cancer Screening and its Prophylactic Vaccination Against Human Papillomavirus Among the Undergraduate Medical Students in a Tertiary Care Hospital - Gandhi, Ramya; Selvaraj, Nitya; Janarthanan, Ilamparithi (Annals of Pathology and Laboratory Medicine, 2018)
Background: Cervical cancer is the second most common malignancy in females and Human papilloma virus[HPV] is the main etiological factor of cervical cancer and it is an important public health issues .The aim of this study is to assess the level of awareness and attitude towards cervical cancer screening and its prophylactic HPV vaccination amongst the undergraduate medical students. Methods: It is a cross sectional study and it was conducted by the Department of Pathology and Pharmacology at Sri Manakula Vinayagar Medical College and hospital ,Puducherry in south India by involving the M.B.B.S undergraduate students from July 2017 to August 2017. Totally 400 students were consented from second year to final year for this study ,a validated and pre-tested questionnaires were filled by them . Result: It was observed that majority of the participants were in the age group of 20- 21 and male participants (50.3%) were higher than female participants ( 49.7%). Majority of the participants were from 5th semester(41.5%), 7th semester(26.5%), 9th semester (25.8%) compared to the 6th and 8th semester. 96.8% of the participants showed positive attitude about their knowledge on cervical cancer and 91.5% regarding pap smear and 55% for HPV vaccination. Very few students 7% had already taken vaccine with no significant differences between the various semesters of medical students. Conclusion: In conclusion the Knowledge and attitude of the participants were positive and high .But only few students had vaccination .Thus ,more knowledge about cervical cancer, pap smear screening and HPV vaccination campaign services can be provided among the medical students.